Characterization and optimization of a steel beam to RC wall connection for use in innovative hybrid coupled wall systems. (February 2020) - Das, R.; Steensels, R.; Dragan, D.; Vandoren, B.; Degée, H.
Abstract: Steel-concrete hybrid solutions with replaceable fuses as coupling elements and appropriately detailed composite connections have shown their efficiency to design safe and easily repairable earthquake-resisting structures. In this general framework, the behavior of a possible steel to concrete composite connection to be used in a recently suggested Hybrid Coupled Wall (HCW) system, consisting of a reinforced concrete shear wall coupled with steel side columns via dissipative steel shear links, is studied in this paper. The steel shear links are bolted to a steel profile either partly embedded or passing through the RC wall. The connection zone is designed in such a way that the damage always occurs in the steel shear links (fuses) prior to any damage in the RC wall in general and in the connection zone in particular. The emphasis lies therefore on the characterization of a suitable "steel link + embedded composite connection within the RC wall" configuration and on the evaluation of an appropriate embedment length allowing the concentration of seismic damage to the replaceable steel links. To this purpose, two joint configurations are designed based on a capacity-based approach, namely "partly embedded" and "completely passing through" steel beam, and are examined through detailed FE analyses. A parametric study is carried out to provide sufficient insight into the system in terms of strength, stiffness and local bearing strength, in view of validating the proposed design procedure.